A Survey on Impact of AI and Social Media for Rural Development - Sarangi, Smruti Smaraki; Singha, Gyanendra (International Journal of Computer Sciences and Engineering, 2025)
Today’s era is considered as an age of science, technology, communication, intelligence, education and economy. The human being is tried to develop the society by implementing and adapting these concepts, especially in villages, city and town and turn them into Smart Village, Smart city and Smart Town. So, the objective of this survey paper is to discuss the impact of artificial intelligence and social media in rural areas for the development purposes, which is located outside of cities or town which is also known as villages. This paper puts light on the relationship of AI and Social media with rural development, that how to improve the rural areas by implementing various technology related to AI and social media.